Pembelajaran Leading By Example: Analisis Keterampilan Mengajar Calon Guru - Lina Arifah Fitriyah; Febi Dwi Widayanti (Universitas Cokroaminoto Palopo, 2023)
This study aims to describe leading by example and conventional learning and to determine the effect on prospective teacher learning outcomes in their teaching abilities. The study was conducted using two samples, namely experimental subjects who were taught using leading by example and control subjects who were taught conventionally. The subjects of this study were prospective teachers in the education study program, as much 15 experimental subjects and 12 control subjects. The research instruments used were lesson plans assessment sheets, media assessment sheets, and teaching skills assessment sheets and learning outcomes (posttest). The research data were analyzed using the independent sample T test. The results showed that prospective teachers who were taught leading by example had an average learning value higher than prospective teachers who were taught conventionally with the results of hypothesis testing obtained t count > t table and a significance value <0.05. This means that there is a difference in the average learning outcomes of experimental subjects and control subjects. Thus the use of leading by example is considered good for application in learning because lecturers as leaders in learning must be able to be a mirror in teaching teaching practice, planning lessons, monitoring learning to carry out learning evaluations for prospective teachers..